A arbitragem como método adequado de solução de conflitos administrativos - Sá, Laila Lacerda de (2021)
This paper aims to answer the following question: does arbitration present itself as an adequate method of resolving conflicts in Public Administration? For that, the pyramidal analysis method was adopted, starting from the foundation, from the historical contextualization of the state's operating mode in the provision of public policies, today characterized by the increasing presence of the private sector, and goes through the analysis of the conflict arising from this legaladministrative relationship. In advance, it goes through the conceptualization and legal nature of arbitration, the benefits for public administration, its position as an instrument for implementation of public policies and the perspective of administrative arbitration within the law and economics. The last station of the trip is the evolvement of administrative arbitration in Portugal and Brazil. The full understanding of the conclusions of each one of the chapters is crucial for arbitration to consolidate itself as one of the methods of the multi-door system of conflict resolution that the Public Administration can and should make use of. The paper ends with a critical analysis of the reasons why administrative arbitration in Brazil did not have the same breath as in Portugal, taking the opportunity to present hypotheses that justify the little promotion of arbitration in Brazil, while its presented solutions that enable, gradually, the implementation of a new culture of conflict resolution in administrative headquarters.